EFFECT OF COMMUNICATION, MOTIVATION AND WORK COMPETENCY ON EMPLOYEE PERFORMANCE - Djadjat Suswanto; Weti Kurniawati; Mahfud (Journal Of Resource Management, Economics And Business, 2022)
Purpose: This study was to determine the effect of communication, motivation and work competency on employee performance. Research Methodology: This research is a quantitative research with regression. This study uses a quantitative approach to see the causal relationship of several factors that influence performance. The population is the object and subject that meet certain criteria related to the problem of a study. The population in this study were all employees of class II Bandung port health office as many as 66 employees. Results: From the calculation results, the calculated F value is 13,438 and the significance is 0.000. Based on the criteria for the F TEST test results, it shows that F count (13,438) > F table (2,76) and the value of Sig (0,000) < 0,05 means that there is an influence between Communication Variables (X 1 ), Motivation (X 2 ) and Competence Work (X 3 ) has a joint (simultaneous) effect on the performance variable (Y). From the results of the analysis of determination (R Square (R2 ) ) shows the coefficient of determination (KD). R2 value of 0.394 means that the percentage of the contribution of the influence of the Communication variable (X 1 ), motivation (X 2 ) and Work Competence (X 3 ) Simultaneously to the Performance variable (Y) is 39.4%. While 60.6% is influenced by other factors. Limitations: The population in this study are all class II Bandung port health office employees, in the future it is hoped that it can be applied in other sectors Contribution: Although the influence of the independent variable on the dependent variable is included in the Less classification. According to the author's suggestion, it should be further improved, especially in terms of communication skills, then the motivation that must be increased and no less important is the Work Competence of the employees themselves, so this will have an impact on increasing employee performance. This will improve health services.